A method for manufacturing a solar cell

By using compounds of general formula (I) as SAM materials in perovskite solar cells, the interface problem between the transparent conductive layer and the light-absorbing layer was solved, improving charge transport and stability, and achieving higher photoelectric conversion efficiency and long-term stability.

CN116634840BActive Publication Date: 2026-11-06ZHEJIANG AIKO SOLAR ENERGY TECH CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310601682.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-25
Publication Date
2026-11-06
Estimated Expiration
2043-05-25

AI Technical Summary

Technical Problem

In the existing technology, the efficiency and stability of perovskite solar cells are insufficient, mainly due to problems such as poor wettability of the substrate transparent conductive layer, large surface roughness of the HTL material, high energy level barrier between HTL and perovskite active layer, and interfacial reaction between perovskite material and hole material, which limit the device efficiency and long-term stability.

Method used

Compounds with general formula (I) are used as self-assembled monolayer (SAM) materials to modify the transparent conductive layer and light-absorbing layer of solar cells. SAMs are prepared by spin coating and other methods to regulate charge separation and transport at the interface and passivate surface defects.

Benefits of technology

It effectively improves charge transport at the interfaces of each layer of the solar cell, passivates surface vacancy defects, and improves the photoelectric conversion efficiency and stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116634840B_ABST
    Figure CN116634840B_ABST
Patent Text Reader

Abstract

This invention relates to the field of solar cells and provides a method for preparing a solar cell, comprising the following steps: growing a transparent conductive layer on a substrate layer; preparing a first SAM comprising a compound having general formula (I) on the transparent conductive layer; preparing a light-absorbing layer; and preparing a metal electrode; wherein the general formula (I) is as follows, wherein R1 is selected from alkyl groups having 1 to 10 carbon atoms, olefins having 1 to 10 carbon atoms, or alkyl groups having 1 to 10 carbon atoms comprising 1 to 3 heteroatoms selected from S, N, or O; R2 is selected from hydrogen or alkyl groups having 1 to 10 carbon atoms; R3 is selected from -COOH, -COOR4, -CONHR4, -CON(R4)2, -SOOH, -SO2OH, -SONHR4, -SON(R4)2, -SO2NHR4, or -SO2N(R4)2; and R4 is selected from alkyl groups having 1 to 10 carbon atoms. The first SAM is used to modify the transparent conductive layer and the light-absorbing layer of the solar cell to effectively improve charge transport at the interface of each layer and passivate vacancy defects on the surface of each layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solar cells, and particularly relates to a method for preparing a solar cell including SAM. Background Technology

[0002] As concerns about future energy supplies continue to grow, so does interest in solar energy. Perovskite solar cells (PSCs) have attracted widespread attention due to their excellent photoelectric properties, such as tunable bandgap, high light absorption coefficient, long carrier lifetime and diffusion length, high defect tolerance, and low-cost low-temperature liquid-phase preparation method, and are expected to become the next generation of new photovoltaic materials.

[0003] However, the efficiency and stability of perovskite solar cells (PSCs) remain significant issues for their commercial application. Currently, the main materials used for hole transport layers (HTLs) in perovskite solar cells are organic materials and metal oxides. However, current PSCs suffer from several problems: poor wettability of the transparent conductive oxide (TCO) substrate, high surface roughness of the HTL material, poor stability of the HTL material, high energy level barriers between the HTL and the perovskite active layer, and interfacial reactions between the perovskite material and the hole material. These problems all affect the efficiency and long-term stability of perovskite solar cell devices. Currently, much research is focused on developing self-assembled monolayers (SAMs) to modify TCO layers or HTLs. The main functions of SAMs include: 1) improving the wettability of the substrate TCO, allowing the perovskite precursor solution to spread effectively, thereby preparing high-quality perovskite films; 2) modifying the energy level matching at the interface to achieve efficient charge separation and transport, improving device efficiency; and 3) passivating ions at the interface, improving device stability.

[0004] Due to the inherent instability of organic high-performance liquid layers (HTLs), inorganic HTLs have been extensively studied, exhibiting better stability compared to organic layers. For example, among numerous metal oxides, Cu₂O is an ideal material with excellent hole mobility and a suitable maximum valence band. Articles have reported the fabrication of pin-type perovskite cascade capacitors (PSCs) based on Cu₂O HTLs (J. Phys. Chem. C 2016, 120, 1428-1437; Small 2015, 11, 5528-5532). Although the HTLs in these device structures are relatively stable, the large surface roughness of the Cu₂O film and the energy level barrier difference between the HTL and the perovskite active layer lead to significant interfacial recombination, thus affecting the improvement of device efficiency.

[0005] Furthermore, existing technologies have reported the use of PTAA(a) / 2PACz(b) (structure as follows) As a SAM material, it is used to modify the interface between the ITO layer and the perovskite active layer or the HTL layer and the perovskite active layer in organic solar cells (CCS Chem. 2022, 1-13, Chemical Linkage and Passivation at Buried Interface for Thermally Stable Inverted Perovskite Solar Cells with Efficiency over 22%). However, the materials used in the prior art still cannot produce solar cells that meet the requirements of photoelectric conversion efficiency and stability in the photovoltaic industry. Summary of the Invention

[0006] This invention provides a method for preparing a solar cell, aiming to solve the problem that existing technologies cannot produce solar cells that meet the photovoltaic industry's requirements for photoelectric conversion efficiency and stability.

[0007] The present invention is implemented as follows: a method for preparing a solar cell includes the following steps:

[0008] A transparent conductive layer is grown on the substrate;

[0009] A first SAM comprising a compound having general formula (I) is prepared on the transparent conductive layer;

[0010] Preparation of light-absorbing layer;

[0011] Preparation of metal electrodes;

[0012] The general formula (I) is as follows:

[0013]

[0014] R1 is selected from alkyl groups having 1 to 10 carbon atoms, olefins having 1 to 10 carbon atoms, or alkyl groups having 1 to 10 carbon atoms including 1 to 3 heteroatoms selected from S, N, or O.

[0015] R2 is selected from hydrogen or alkyl groups having 1 to 10 carbon atoms;

[0016] R3 is selected from -COOH, -COOR4, -CONHR4, -CON(R4)2, -SOOH, -SO2OH, -SONHR4, -SON(R4)2, -SO2NHR4 or -SO2N(R4)2;

[0017] R4 is selected from alkyl groups having 1 to 10 carbon atoms.

[0018] Furthermore, in the compound,

[0019] R1 is selected from alkyl groups having 1 to 6 carbon atoms or including 1 to 3 alkyl groups having 1 to 6 carbon atoms selected from S, N or O heteroatoms;

[0020] R2 is selected from hydrogen or an alkyl group having 1 to 5 carbon atoms; and

[0021] R4 is selected from alkyl groups having 1 to 5 carbon atoms.

[0022] Furthermore, in the compound, R1 is selected from a straight-chain alkyl group having 1 to 3 carbon atoms or an alkyl group having 1 to 3 carbon atoms including a heteroatom selected from S, N or O.

[0023] Furthermore, in the compound, R2 is selected from hydrogen or a straight-chain alkyl group having 2 to 4 carbon atoms.

[0024] Furthermore, in the compound, R4 is selected from straight-chain alkyl groups having 2 to 4 carbon atoms.

[0025] Furthermore, it also includes preparing a hole transport layer on the transparent conductive layer before preparing the first SAM, such that the first SAM is disposed between the hole transport layer and the light absorption layer, and the hole transport layer is prepared by spin coating, blade coating, slot deposition, spraying, evaporation, magnetron sputtering or electrochemical deposition.

[0026] Furthermore, the first SAM is prepared by vapor deposition, spin coating, blade coating, slot deposition, spraying, solution dip coating, or vapor deposition.

[0027] Furthermore, the method also includes preparing an electron transport layer on the light absorption layer, such that the electron transport layer is disposed between the light absorption layer and the metal electrode, and the electron transport layer is prepared by spin coating, blade coating, slot deposition, spraying, vapor deposition, magnetron sputtering or electrochemical deposition.

[0028] Furthermore, the method also includes preparing a second SAM on the light-absorbing layer, such that the second SAM is disposed between the light-absorbing layer and the electron transport layer, and the second SAM is made of the compound having the general formula (I), PTAA-type SAM material, 2PACz-type SAM material or ImAcHCl.

[0029] Furthermore, the light-absorbing layer is made of cuprous oxide, perovskite material, or organic active material.

[0030] Furthermore, the light-absorbing layer is made of perovskite material, in which case the light-absorbing layer is a perovskite active layer, and the perovskite thin film is prepared by a one-step or two-step method, and then annealed to obtain the perovskite active layer.

[0031] Furthermore, the perovskite material has the general molecular structure formula ABX3, wherein A is selected from one or more of methylamine ions, formamidinium ions, phenylethylamine ions, 1-naphthylmethylamine ions, and cesium ions; and B is selected from Pb. 2+ and Sn 2+ One or more of them; X is selected from I - ,Br - and Cl - One or more of them.

[0032] Furthermore, the one-step method includes preparing the perovskite thin film using a wet or dry method.

[0033] Furthermore, the wet process includes first preparing a perovskite precursor solution, and then preparing the perovskite thin film from the perovskite precursor solution by spin coating, blade coating, spray coating or inkjet printing; the dry process is vapor deposition, physical vapor deposition or chemical vapor deposition.

[0034] Furthermore, the two-step method includes first preparing a first perovskite film using the inorganic phase of the perovskite material; and then forming a second perovskite film on the first perovskite film using the organic phase of the perovskite material.

[0035] The first perovskite film and the second perovskite film constitute the perovskite active layer.

[0036] Furthermore, the first perovskite film and the second perovskite film are prepared using a wet or dry method;

[0037] The wet process includes first preparing a perovskite precursor solution, and then preparing the perovskite precursor solution into the first perovskite film or the second perovskite film by spin coating, blade coating, spray coating or inkjet printing; the dry process is vapor deposition, physical vapor deposition or chemical vapor deposition.

[0038] Furthermore, in the two-step method, the process of preparing the second perovskite film using a wet method includes: mixing the organic phase of the perovskite material with the compound having general formula (I) to prepare a perovskite precursor solution.

[0039] Furthermore, in the perovskite precursor solution, the concentration of the compound is between 0.1 mg / mL and 1.0 mg / mL.

[0040] Furthermore, the method also includes preparing an interface layer on the electron transport layer, such that the interface layer is disposed between the electron transport layer and the metal electrode, and the interface layer is prepared by spin coating, blade coating, slot deposition, spraying, vapor deposition, magnetron sputtering or electrochemical deposition.

[0041] Furthermore, the annealing temperature is between 100°C and 150°C, and the annealing time is between 10 min and 30 min.

[0042] Thanks to the preparation method according to the present invention, which includes the preparation of a first SAM, the first SAM is used to modify the transparent conductive layer and the light-absorbing layer of the solar cell, so as to effectively improve the charge transport at the interface of each layer and passivate the vacancy defects on the surface of each layer. Attached Figure Description

[0043] Figure 1 This is a schematic diagram of the perovskite solar cell device structure provided in Example 6.

[0044] Figure 2 This is a schematic diagram of the perovskite solar cell device structure provided in Example 7.

[0045] Figure 3 This is a schematic diagram of the solar cell device structure provided in Example 8.

[0046] Figure 4 This is a schematic diagram of the solar cell device structure provided in Example 9.

[0047] Figure 5 This is a schematic diagram of the perovskite solar cell device structure provided in Example 10.

[0048] Figure 6 This is a schematic diagram of the perovskite solar cell device structure provided in Example 11.

[0049] Figure 7 This is a schematic diagram of the perovskite solar cell device structure provided in Example Twelve.

[0050] Wherein, S0 is the substrate layer; S1 is the transparent conductive layer (TCO); S2 is the hole transport layer (HTL); S31 is the first SAM; S32 is the second SAM; S41 is the perovskite active layer; S42 is the cuprous oxide active layer; S5 is the electron transport layer (ETL); S6 is the interface layer; and S7 is the metal electrode. Detailed Implementation

[0051] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0052] Example 1

[0053] This embodiment provides a compound having the general formula (I):

[0054]

[0055] R1 is selected from alkyl groups having 1 to 10 carbon atoms, olefins having 1 to 10 carbon atoms, or alkyl groups having 1 to 10 carbon atoms including 1 to 3 heteroatoms selected from S, N, or O.

[0056] R2 is selected from hydrogen or alkyl groups having 1 to 10 carbon atoms;

[0057] R3 is selected from -COOH, -COOR4, -CONHR4, -CON(R4)2, -SOOH, -SO2OH, -SONHR4, -SON(R4)2, -SO2NHR4 or -SO2N(R4)2;

[0058] R4 is selected from alkyl groups having 1 to 10 carbon atoms.

[0059] Preferably, R1 is selected from alkyl groups having 1 to 6 carbon atoms or including 1 to 3 alkyl groups having 1 to 6 carbon atoms selected from S, N or O heteroatoms;

[0060] R2 is selected from hydrogen or an alkyl group having 1 to 5 carbon atoms; and

[0061] R4 is selected from alkyl groups having 1 to 5 carbon atoms.

[0062] More preferably, R1 is selected from a straight-chain alkyl group having 1 to 3 carbon atoms or an alkyl group having 1 to 3 carbon atoms including a heteroatom selected from S, N or O. More preferably, R2 is selected from hydrogen or a straight-chain alkyl group having 2 to 4 carbon atoms. More preferably, R4 is selected from a straight-chain alkyl group having 2 to 4 carbon atoms.

[0063] The possible choices for compounds having the general formula (I) are as follows:

[0064]

[0065]

[0066] The compounds of general formula (I) according to the present invention are suitable for use in the fabrication of solar cells, and particularly suitable as SAM materials to modify one or more of the transparent conductive layer, light-absorbing layer, and hole transport layer of solar cells. SAM, or self-assembled monolayer, refers to a crystalline, chemically absorbing organic monolayer formed on a solid substrate through the spontaneous organization of molecules. SAM materials refer to compounds capable of forming SAM. The phrase "modifying one or more of the transparent conductive layer, light-absorbing layer, and hole transport layer of solar cells" refers to passivating surface defects in these layers, adjusting the work function, and promoting charge separation and transport at the interfaces of these layers.

[0067] In existing technologies, phosphate groups are mainly used as functional groups for triphenylamine. However, phosphate groups are acidic and corrosive to the transparent conductive layer. This invention selects phosphate ester groups as functional groups for triphenylamine, avoiding the corrosion of the transparent conductive layer by the SAM material, while simultaneously modifying other layers. The compounds according to this invention use triphenylamine as the core, introducing functional groups at various active sites, thereby deriving a series of triphenylamine-type SAM materials with self-assembly capabilities. Such SAM materials possess excellent hole transport, self-spreading, and anchoring abilities, and can be widely used to modify the transparent conductive layer, hole transport layer, and light-absorbing layer of solar cells, effectively improving charge transport at the interfaces of each layer and passivating vacancy defects on the surface of each layer.

[0068] Example 2

[0069] This embodiment provides a method for preparing a compound having general formula (I) according to the present invention, the synthetic route of which is shown below.

[0070]

[0071] The specific reaction steps are as follows:

[0072] Compound D1 Compound M1 is generated by a nucleophilic reaction; preferably, compounds D1 and D2 are reacted at 30°C to 70°C for 5 to 15 hours in the presence of a palladium catalyst to generate compound M1.

[0073] The compound M1 Reaction with brominating reagent to form a compound Preferably, compound M1 reacts with N-bromosuccinimide (NBS) at -20°C to 20°C for 2 to 10 hours to generate compound M2;

[0074] Compound M2 is converted into compound M3 through a substitution reaction. Preferably, compound M2 reacts with phosphite ester at 100°C to 200°C for 2 hours to 20 hours to generate compound M3.

[0075] The compound M3 undergoes a substitution reaction to generate a compound having the general formula (I). Preferably, compound M3 is reacted with a palladium catalyst at 80°C to 150°C for 8 to 20 hours to produce the compound having the general formula (I).

[0076] Example 3

[0077] This embodiment provides compound M41 The preparation method of compound M41 is a specific embodiment of a compound having the general formula (I). The synthetic route of compound M41 is as follows:

[0078]

[0079] Specifically, it includes the following steps.

[0080] Step L1:

[0081] Raw materials D11 (3 g, 11.5 mmol), D2 (1.94 g, 11.5 mmol), sodium tert-butoxide (2.20 g, 23.0 mmol), tris(dibenzylacetone)dipalladium (209.7 mg, 0.23 mmol), tri-tert-butylphosphine tetrafluoroborate (266 mg, 0.92 mmol), and ultradry toluene were added to a round-bottom flask under nitrogen protection after evacuation. The reaction mixture was heated to 50 °C and reacted for 10 h, then cooled to room temperature. After filtration, the solvent and volatiles were removed by rotary evaporation. Subsequently, a solid crude product was obtained, which was subjected to column chromatography (PE:DCM) to give the target product M11 (3.54 g, 88.4%).

[0082] 1H NMR (500MHz, CDCl3): δ 7.24 (m, 4H), 7.18 (m, 2H), 7.10-7.06 (m, 4H), 7.04-6.98 (m, 4H), 3.65 (t, 2H), 3.00 (t, 2H).

[0083] Step L2:

[0084] The process product M11 (2 g, 5.68 mmol) was dissolved in a mixed solvent of DMF and THF and cooled in an ice-water bath for 30 min. N-bromosuccinimide (NBS, 2.04 g, 11.47 mmol) was added to the above reaction solution in several portions, and the reaction was maintained at 0 °C for 5 h. The reaction end time was confirmed by TLC. Subsequently, the reaction was quenched with sodium thiosulfate solution, and the reaction solution was extracted with DCM. The organic phase was concentrated and then subjected to column chromatography (PE:DCM) to obtain the target product M21 (2.70 g, 93.2%).

[0085] 1H NMR (400MHz, CDCl3): δ7.38 (m, 4H), 7.18 (m, 2H), 7.10-7.06 (m, 4H), 7.04-6.98 (m, 2H), 3.65 (t, 2H), 3.00 (t, 2H).

[0086] Step L3:

[0087] Process product M21 (2 g, 3.92 mmol) was added to a dry reaction flask, and the mixture was evacuated and protected with nitrogen. Triethyl phosphite (10 ml) was then added, and the mixture was heated to 150 °C and reacted for 12 h. After the reaction was completed, unreacted triethyl phosphite was removed by vacuum distillation, and the crude product was subjected to column chromatography (DCM:EA) to obtain the target product M31 (1.82 g, 81.8%).

[0088] 1H NMR (500MHz, CDCl3): δ7.38 (m, 4H), 7.18 (m, 2H), 7.10-7.06 (m, 4H), 7.04-6.98 (m, 2H), 4.20 (d, 4H), 2.65 (t, 2H), 2.10 (t, 2H), 1.36 (t, 6H).

[0089] Step L4:

[0090] Process product M31 (2.27 g, 4.0 mmol), methyltetrahydrofuran (6 mL), Pd / Co3O4–Li catalyst (0.6 g), triethylamine (0.809 g, 8 mmol), and formic acid (6 mL) were added to a reaction flask and heated under reflux at 120 °C for 12 h. Subsequently, methylamine (6 mL) was added to the system, and the reaction continued for 2 h. After the reaction was complete, the mixture was cooled to room temperature, and 50 mL of deionized water was added. The organic phase was separated using a separatory funnel and extracted three times with ethyl acetate. The organic phase was collected, washed with saturated sodium chloride solution, and dried over anhydrous magnesium sulfate. The filtrate was filtered, and the solvent was removed by rotary evaporation to obtain the crude product. The crude product was then purified by column chromatography (PE:EA:MeOH) to obtain the target product M41 (1.58 g, 75.4%).

[0091] 1H NMR (500MHz, CDCl3): δ8.28(m, 2H), 7.65(m, 4H), 7.36(m, 4H), 7.18(m, 2H), 7.04 -6.98(m, 2H), 4.20(d, 4H), 2.80(s, 6H), 2.65(t, 2H), 2.10(t, 2H), 1.36(t, 6H).

[0092] Example 4

[0093] This embodiment provides compound M42 The preparation method of compound M42 is a specific embodiment of a compound having the general formula (I). In the specific preparation method of compound M42, steps L1 to L3 are as shown in Example 2, the difference being step L4:

[0094]

[0095] Step L4:

[0096] Process product M31 (2.27 g, 4.0 mmol), methyltetrahydrofuran (6 mL), Pd / Co3O4–Li catalyst (0.6 g), triethylamine (0.809 g, 8 mmol), and formic acid (6 mL) were added to a reaction flask and heated under reflux at 120 °C for 12 h. After the reaction was completed, the mixture was cooled to room temperature, and 50 mL of deionized water was added. The organic phase was separated using a separatory funnel and extracted with ethyl acetate three times. The organic phase was collected, washed with saturated sodium chloride solution, and dried with anhydrous magnesium sulfate after separation. The filtrate was filtered, and the solvent was removed by rotary evaporation to obtain the crude product. Recrystallization yielded the target product M42 (1.62 g, 81.4%).

[0097] 1H NMR (500MHz, CDCl3): δ 7.90 (m, 4H), 7.36 (m, 4H), 7.18 (m, 2H), 7.04-6.98 (m, 2H), 4.20 (d, 4H), 2.65 (t, 2H), 2.10 (t, 2H), 1.36 (t, 6H).

[0098] Example 5

[0099] This embodiment provides compound M43. The preparation method of compound M43 is described below. Compound M43 is a specific embodiment of a compound having the general formula (I). The synthetic route of compound M43 is as follows:

[0100]

[0101] And it includes the following specific steps.

[0102] Step L1:

[0103] Raw materials D13 (3.22 g, 11.5 mmol), D2 (1.94 g, 11.5 mmol), sodium tert-butoxide (2.20 g, 23.0 mmol), tris(dibenzylacetone)dipalladium (209.7 mg, 0.23 mmol), tri-tert-butylphosphine tetrafluoroborate (266 mg, 0.92 mmol), and ultradry toluene were added to a round-bottom flask under nitrogen protection after evacuation. The reaction mixture was heated to 50 °C and reacted for 10 h, then cooled to room temperature. After filtration, the solvent and volatiles were removed by rotary evaporation. Subsequently, a solid crude product was obtained, which was subjected to column chromatography (PE:DCM) to give the target product M13 (3.8 g, 89.73%).

[0104] 1H NMR (500MHz, CDCl3): δ 7.24 (m, 4H), 7.18 (m, 2H), 7.10-7.06 (m, 4H), 7.04-6.98 (m, 4H), 4.33 (t, 2H), 3.79 (t, 2H).

[0105] Step L2:

[0106] The process product M13 (2.09 g, 5.68 mmol) was dissolved in a mixed solvent of DMF and THF and cooled in an ice-water bath for 30 min. N-bromosuccinimide (NBS, 2.04 g, 11.47 mmol) was added to the above reaction solution in several portions, and the reaction was maintained at 0 °C for 5 h. The reaction end time was confirmed by TLC. Subsequently, the reaction was quenched with sodium thiosulfate solution, and the reaction solution was extracted with DCM. The organic phase was concentrated and then subjected to column chromatography (PE:DCM) to obtain the target product M23 (2.72 g, 91.3%).

[0107] 1H NMR (400MHz, CDCl3): δ 7.38 (m, 4H), 7.18 (m, 2H), 7.10-7.06 (m, 4H), 7.04-6.98 (m, 2H), 4.33 (t, 2H), 3.79 (t, 2H).

[0108] Step L3:

[0109] Process product M23 (2.06 g, 3.92 mmol) was added to a dry reaction flask, and the mixture was evacuated and protected with nitrogen. Triethyl phosphite (10 ml) was then added, and the mixture was heated to 150 °C and reacted for 12 h. After the reaction was completed, unreacted triethyl phosphite was removed by vacuum distillation, and the crude product was subjected to column chromatography (DCM:EA) to obtain the target product M33 (1.92 g, 84.0%).

[0110] 1H NMR (500MHz, CDCl3): δ 7.38 (m, 4H), 7.18 (m, 2H), 7.10-7.06 (m, 4H), 7.04-6.98 (m, 2H), 4.20-4.18 (t, 6H), 2.20 (t, 2H), 1.36 (t, 6H).

[0111] Step L4:

[0112] Process product M33 (2.33 g, 4.0 mmol), 6 mL of methyltetrahydrofuran, Pd / Co3O4–Li catalyst (0.6 g), triethylamine (0.809 g, 8 mmol), and ethyl chlorosulfonate (1.28 g, 10.0 mmol) were added to a reaction flask and heated to reflux at 120 °C for 12 h. After the reaction was completed, the mixture was cooled to room temperature, and 50 mL of deionized water was added. The organic phase was separated using a separatory funnel and extracted with ethyl acetate three times. The organic phase was collected, washed with saturated sodium chloride solution, and dried with anhydrous magnesium sulfate after separation. The filtrate was filtered, and the solvent was removed by rotary evaporation to obtain the crude product. The crude product was purified by column chromatography (PE:EA:MeOH) to obtain the target product M43 (1.65 g, 67.7%).

[0113] 1H NMR (500MHz, CDCl3): δ7.45(m, 4H), 7.38(m, 4H), 7.18(m, 2H), 7.04-6.98(m, 2H), 4.20-4.18(t, 6H), 3.57(t, 4H), 2.20(t, 2H), 1.36(t, 6H), 1.10(t, 6H).

[0114] Example 6

[0115] This embodiment provides a perovskite solar cell device comprising a compound having general formula (I) according to the present invention, such as... Figure 1 As shown, the device, from bottom to top, includes: a substrate layer S0; a transparent conductive layer S1 grown on the substrate layer S0; a hole transport layer S2; a first SAM S31; a perovskite active layer S41; an electron transport layer S5; an interface layer S6; and a metal electrode S7.

[0116] This embodiment also provides a method for fabricating a perovskite solar cell, referring to... Figure 1 This includes the following steps:

[0117] a. Growing a transparent conductive layer on the substrate.

[0118] In this embodiment, the substrate S0 is high-transparency glass or fluorinated glass; the transparent conductive layer S1 is made of ITO, FTO, IZO, AZO, ATO, IWO, IWO or ICO, and in this embodiment it is made of FTO. The preparation method of the TCO layer includes, but is not limited to, magnetron sputtering, and the deposition thickness is between 10 nm and 100 nm.

[0119] b. Preparation of hole transport layer

[0120] In this embodiment, the hole transport layer S2 is made of Cu2O. Generally, Cu2O has excellent hole mobility and a suitable maximum valence band, making it an ideal material for preparing HTLs. However, due to the instability of perovskite materials and the interfacial reaction between the perovskite and hole transport layer materials, degradation of the perovskite active layer is common, thus affecting the long-term stability of the device and the photoelectric conversion efficiency of the solar cell.

[0121] In other embodiments, the hole transport layer S2 may also be made of other inorganic hole transport materials, such as NiO. X The hole transport layer S2 is prepared using any one of the following materials: TiO2, Nb2O5, CuSCN, CuI, and V2O5. The preparation method of the hole transport layer S2 includes, but is not limited to, spin coating, blade coating, slot deposition, spraying, evaporation, magnetron sputtering, electrochemical deposition, and any suitable method in the prior art. The thickness of the hole transport layer S2 is between 10 nm and 100 nm.

[0122] c. Preparation of the first SAM

[0123] In this embodiment, the first SAM S31 is a self-assembled monolayer (SAM) made from a compound having general formula (I) according to the present invention. Specifically, in this embodiment, it is compound M41. It is understood that in other embodiments, the first SAM may also be made from other compounds having general formula (I), such as the specific compounds listed in Example 1 above.

[0124] In this embodiment, the first SAM was prepared using a solution spraying method, including preparing a SAM solution (0.1 mg / mL), delivering the SAM solution at a flow rate of 1.5 mL / min, with the spray nozzle approximately 3 cm from the substrate, and a spraying speed of 40 mm / s. After SAM deposition, while the film was still wet, the sprayed substrate was immersed in ethanol and immediately rinsed once to obtain optimal performance. The substrate was then dried under a nitrogen stream and annealed at 100°C for 10 min. After annealing, the substrate was continuously rinsed three times in ethanol and then dried under a nitrogen stream.

[0125] In other embodiments, the preparation method of the first SAM S31 includes, but is not limited to, vapor deposition, spin coating, blade coating, slot deposition, spraying, solution pulling, and vapor deposition. The thickness of the first SAM S31 is between 1 nm and 20 nm.

[0126] d. Preparation of perovskite active layer

[0127] In this embodiment, the perovskite active layer S41 is prepared by a one-step method, specifically a wet one-step method, and the specific steps are as follows.

[0128] Before preparing the perovskite active layer, the hole transport layer was surface-treated for 10 min using a UV / ozone cleaner. Then, a 1.6 mol / L perovskite precursor solution was prepared in a mixed solvent of DMF and DMSO (4:1 v / v). 35 μL of the perovskite precursor solution was dropped onto the substrate layer covering the hole transport layer and the transparent conductive layer, and spin-coated at 6000 rpm / min for 60 s. After 40 s of spin-coating, 1 mL of diethyl ether solution was added, followed by annealing at 130 °C for 20 min on a hot plate. After crystallization, the perovskite active layer was formed. The thickness of the perovskite active layer S41 was between 50 nm and 1000 nm.

[0129] It is understood that, in other embodiments, the method for preparing the perovskite active layer can be any of the prior art, such as spin coating, blade coating, slot deposition, spray coating, inkjet printing, or vapor deposition. The method for preparing the perovskite active layer can also be a two-step method.

[0130] In addition, the perovskite active layer S41 in this embodiment can be made of perovskite material. The general molecular formula of perovskite material is ABX3, wherein A is selected from one or more of methylamine ion, formamidinium ion, phenylethylamine ion, 1-naphthylmethylamine ion and cesium ion; B is selected from Pb 2+ and Sn 2+ One or more of them; X is selected from I - ,Br - and Cl - One or more of these. For example, for organic-inorganic hybrid perovskites, the general formula is Cs. a FA b MA c Pb(I x Br y Cl z )3, where 0≤a,b,c≤1, and a+b+c=1, x+y+z=1; for all inorganic perovskites, the general molecular formula of perovskite is CsPb(I a Br b3, where 0 ≤ a, b ≤ 1, and a + b = 1. In other embodiments, the perovskite active layer can also be any other suitable perovskite material.

[0131] e. Fabrication of electron transport layer

[0132] In this embodiment, the electron transport layer (ETL) S5 is made of an organic electron transport material (such as a fullerene or a fullerene derivative, PCBM). In other embodiments, the electron transport layer may also be made of an inorganic electron transport material (such as SnO2, TiO2).

[0133] The electron transport layer S5 can be prepared by methods including, but not limited to, spin coating, blade coating, slot deposition, spraying, vapor deposition, magnetron sputtering, and electrochemical deposition. The thickness of the electron transport layer S5 is between 10 nm and 100 nm.

[0134] f. Preparation of the interface layer

[0135] In this embodiment, the interface layer S6 is a cathode interfacial layer (CIL), made of organic electron transport materials (such as BCP, PDINO, NDI, PDINN, etc.) or inorganic electron transport materials (such as metal fluorides, ZnO, CsCO3, TiOx, etc.). The preparation methods for the interface layer S6 include, but are not limited to, spin coating, blade coating, slot deposition, spraying, vapor deposition, magnetron sputtering, and electrochemical deposition. The thickness of the interface layer S6 is between 10 nm and 100 nm. The cathode interface layer plays a role in adjusting surface defects and work function between the PCBM and the Ag electrode.

[0136] g. Preparation of metal electrodes

[0137] In this embodiment, the metal electrode S7 is made of Ag. It is understood that in other embodiments, the metal electrode S7 may also be made of one or more of Au, Cu, and Al. The preparation methods of the metal electrode S7 include, but are not limited to, vapor deposition, magnetron sputtering, and solution methods, and the thickness is between 10 nm and 100 nm.

[0138] The perovskite active layer S41 and the hole transport layer S2 suffer from energy level mismatch, resulting in poor stability and reduced photoelectric conversion efficiency. In this embodiment, the first SAM S31 comprises a compound of general formula (I) according to the present invention. The first SAM S31 can passivate surface defects of the HTL, adjust the work function, and promote charge separation and transport at the interface; that is, the first SAM modifies the HTL. Thanks to the presence of SAM, charge transport at the interface between the perovskite active layer and the HTL in the perovskite solar cell is effectively improved, vacancy defects on the surface of the perovskite film are passivated, thereby improving the stability of the HTL and thus improving the photoelectric conversion efficiency of the solar cell.

[0139] Example 7

[0140] This embodiment provides a perovskite solar cell device comprising the compound according to the present invention, such as... Figure 2 As shown, the device comprises, from bottom to top: a transparent conductive layer S1 grown on a substrate layer (not shown in the figure); a first SAM S31 comprising a compound according to the present invention; a perovskite active layer S41; an electron transport layer S5; an interface layer S6; and a metal electrode S7.

[0141] Unlike the embodiments described above, this embodiment does not have an HTL; instead, the first SAM is in direct contact with the transparent conductive layer, and in this case, the first SAM can directly act as an HTL.

[0142] The preparation method of the first SAM S31 in this embodiment is similar to that in the above embodiments, and it also adopts the solution spraying method.

[0143] This embodiment also provides a method for preparing the perovskite active layer of a perovskite solar cell, specifically a two-step method. The perovskite material in this embodiment is an organic-inorganic hybrid perovskite, specifically with the general formula FAPbI3. The specific preparation method is as follows:

[0144] i) Preparation of the first perovskite thin film

[0145] The inorganic phase PbI2 is deposited on the substrate by a dry method, which in this embodiment is achieved by vapor deposition.

[0146] It is understood that in other embodiments, methods such as vapor deposition, spin coating, blade coating, and spray coating can also be used to deposit the first perovskite film.

[0147] ii) Preparation of second perovskite thin films

[0148] Organic phase FAI was dissolved in isopropanol to prepare a perovskite precursor solution. 35 μL of the perovskite precursor solution was dropped onto the first perovskite film (i.e., PbI2 film) prepared in the previous step, and spin-coated at 6000 rpm / min for 60 s. After 40 s of spin-coating, 1 mL of diethyl ether solution was added, followed by annealing at 140 °C for 30 min on a hot plate to obtain the second perovskite film.

[0149] It is understood that, in other embodiments, dry methods, such as vapor deposition, physical vapor deposition, or chemical vapor deposition, can also be used to prepare the second perovskite film.

[0150] The first and second perovskite films constitute the perovskite active layer, and the thickness of the perovskite active layer is between 50 nm and 1000 nm.

[0151] It is understood that the cathode interface layer (CIL) in this embodiment is optional, and in other embodiments, the cathode interface layer may be omitted.

[0152] In this embodiment, the TCO layer is made of FTO. The compound of general formula (I) according to the present invention can be used as a SAM material to modify the TCO layer. It can form covalent bonds with the TCO surface and be directly anchored to the TCO surface to form a monolayer. This first SAM regulates the wettability and work function of the TCO surface, resulting in better film formation from the perovskite solution and a more matched energy level at the interface. Furthermore, the first SAM S31 in this embodiment can directly contact the TCO layer, directly acting as a hole transport layer. The presence of this first SAM can save on the hole transport layer, thus simplifying the production process and reducing production costs.

[0153] Example 8

[0154] This embodiment provides a solar cell device comprising a compound having general formula (I) according to the present invention, such as... Figure 3 As shown, the device, from bottom to top, includes: a transparent conductive layer S1 grown on a substrate; a hole transport layer (HTL) S2; a first SAM S31; a cuprous oxide active layer S42; a second SAM S32; an electron transport layer (ETL) S5; and a metal electrode S7.

[0155] In this embodiment, the light-absorbing layer is made of Cu2O, and is therefore a cuprous oxide active layer S42. Both the top and bottom surfaces of the cuprous oxide active layer S42 are modified with SAM. The first SAM and / or the second SAM comprises compounds having general formula (I) according to the present invention. Furthermore, the SAM materials in the first SAM and the second SAM can be the same or different.

[0156] For example, the first SAM includes compound M41 from the above embodiments, and the second SAM includes the prior art SAM material 2PACz or ImAcHCl (i.e., 4-imidazoleacetic acid hydrochloride). As another example, the first SAM includes compound M41 from the above embodiments, and the second SAM includes compound M42 from the above embodiments. Yet another example, the first SAM includes compound M41 from the above embodiments, and the second SAM also includes compound M41.

[0157] In this embodiment, the thickness of the first SAM and the second SAM is between 1 nm and 20 nm. The thickness of the first SAM and the second SAM depends on the molecular weight of the SAM material, and the thickness is generally the molecular thickness of one layer of SAM material, for example, 5 nm, 10 nm, or 15 nm.

[0158] By modifying the upper and lower SAMs including the compound (I) according to the present invention, the energy level mismatch between the cuprous oxide active layer and the electron transport layer, and between the cuprous oxide active layer and the hole transport layer, can be improved. Similar to the principle of modifying the perovskite active layer, the SAM including the compound (I) according to the present invention can passivate the vacancy defects on the cuprous oxide surface, improve charge transport at the interface, and thereby improve the photoelectric conversion efficiency of the solar cell.

[0159] Example 9

[0160] This embodiment provides a solar cell device comprising a compound having general formula (I) according to the present invention, such as... Figure 4 As shown, the device comprises, from bottom to top: a substrate layer (not shown in the figure), a transparent conductive layer S1 grown on the substrate layer; a first SAM S31; a cuprous oxide active layer S42; a second SAM S32; and a metal electrode S7.

[0161] In this embodiment, both the upper and lower surfaces of the cuprous oxide active layer S42 are modified with SAM. The first SAM and / or the second SAM comprises compounds having general formula (I) according to the present invention. Moreover, the SAM materials in the first SAM and the second SAM can be the same or different.

[0162] For example, the first SAM includes compound M41 from the above embodiments, and the second SAM includes the prior art SAM material 2PACz. As another example, the first SAM includes compound M41 from the above embodiments, and the second SAM includes compound M42 from the above embodiments. Yet another example, the first SAM includes compound M41 from the above embodiments, and the second SAM also includes compound M41.

[0163] Unlike the previous embodiment, this embodiment does not have a hole transport layer and an electron transport layer. Furthermore, the first SAM S31 can directly function as a hole transport layer, and the second SAM S32 can directly function as an electron transport layer.

[0164] It is understood that, in other embodiments, the light-absorbing layer may also be a perovskite active layer made of perovskite material or an organic material active layer made of organic light-absorbing material. For example, the organic light-absorbing material PM6:Y6.

[0165] Modification with compounds of general formula (I) according to the present invention can improve the energy level mismatch between the cuprous oxide active layer and the electron transport layer, and between the cuprous oxide active layer and the hole transport layer. Similar to the principle of modifying perovskite active layers, SAM can passivate vacancy defects on the cuprous oxide surface, improve the stability of the cuprous oxide active layer, and thus improve the photoelectric conversion efficiency of solar cells.

[0166] Example 10

[0167] This embodiment provides a perovskite solar cell device comprising a compound having general formula (I) according to the present invention, such as... Figure 5 As shown, the device comprises, from bottom to top: a substrate layer (not shown in the figure); a transparent conductive layer S1 grown on the substrate layer; a first SAM S31; a perovskite active layer S41; a second SAM S32; an electron transport layer (ETL) S5; an interface layer S6; and a metal electrode S7.

[0168] In this embodiment, the perovskite active layer S41 is modified with a first SAM S31 and a second SAM S32 according to the compound of the present invention on both the upper and lower surfaces.

[0169] In this embodiment, the interface layer is a cathode interface layer (CIL), which plays a role in adjusting surface defects and work function between the ETL and the metal electrode.

[0170] This embodiment also provides a method for preparing a perovskite active layer, a first SAM, and a second SAM. This method is a two-step method, and the specific preparation method is as follows:

[0171] i) Preparation of the first perovskite thin film

[0172] The inorganic phase PbI2 is deposited on the substrate layer by a dry method. In this embodiment, the first perovskite film is obtained by vapor deposition.

[0173] ii) Preparation of second perovskite thin films

[0174] The organic phase FAI of the perovskite material and the compound according to the invention are dissolved in isopropanol to prepare a perovskite precursor solution. In the perovskite precursor solution, the concentration of the compound according to the invention is between 0.1 mg / mL and 1.0 mg / mL, for example, 0.25 mg / mL, 0.5 mg / mL, or 0.75 mg / mL. 35 μL of the perovskite precursor solution is dropped onto the first perovskite film, i.e., the PbI2 film, prepared in the previous step, and spin-coated at 6000 rpm / min for 60 s. After spin-coating for 40 s, 1 mL of diethyl ether solution is added, followed by annealing at 150°C for 10 min on a hot plate to obtain the second perovskite film.

[0175] The preparation method in this embodiment, which involves first preparing a first perovskite film using a dry method and then preparing a second perovskite film using a wet method, can be referred to as a two-step method combining dry and wet methods.

[0176] The first and second perovskite films constitute the perovskite active layer. After the organic and inorganic phases of the perovskite material have completed crystallization, due to the steric hindrance of the perovskite crystals, the compound according to the present invention will eventually be deposited on both the upper and lower surfaces of the perovskite active layer, forming the first SAM S31 and the second SAM S32, as shown below. Figure 5 As shown. Therefore, when the compound according to the invention is added during the preparation of the second perovskite film, the SAM materials of the first SAM S31 and the second SAM S32 are the same. In this embodiment, both the first SAM 31 and the second SAM 32 are made of compound M42.

[0177] Generally, dry perovskite film preparation requires a flat substrate to obtain perovskite films with minimal interface defects. However, a two-step method, especially a combined dry-wet method, can eliminate this requirement for substrate flatness, allowing perovskite films with minimal interface defects to be prepared even on uneven substrates. Furthermore, by adding a certain proportion of SAM material to the organic phase solution of the perovskite material in the combined dry-wet method, the perovskite layer and SAM can be prepared simultaneously, significantly improving production efficiency.

[0178] It is understood that in other embodiments, the first SAM S31, the perovskite active layer S41, and the second SAM S32 can be prepared separately. For example, the first SAM S31 can be prepared using a wet process, the perovskite active layer S41 can be prepared using a two-step method combining wet and dry processes, and the second SAM S32 can be prepared using a wet process. In this case, the SAM materials of the first SAM S31 and the second SAM S32 can be the same or different, and one layer of the first SAM S31 and the second SAM S32 can be made of the compound according to the invention, while the other layer can be made of any suitable SAM material in the prior art; or both the first SAM S31 and the second SAM S32 can be made of the compound according to the invention.

[0179] Example 11

[0180] This embodiment provides a perovskite solar cell device comprising a compound having general formula (I) according to the present invention, such as... Figure 6 As shown, the device, from bottom to top, includes: a transparent conductive layer S1 grown on a substrate; a hole transport layer S2; a first SAM S31; a perovskite active layer S41; a second SAM S32; an electron transport layer (ETL) S5; an interface layer S6; and a metal electrode S7.

[0181] In this embodiment, the hole transport layer S2 is made of NiO. x The first SAM S31 can passivate surface defects in the hole transport layer, adjust the work function, and promote charge separation and transport at the interface. Similar to the above embodiments, the SAM materials in the first SAM S31 and the second SAM S32 in this embodiment can be the same or different. The first SAM S31 and / or the second SAM S32 comprise compounds having general formula (I) according to the present invention.

[0182] Example 12

[0183] This embodiment provides a perovskite solar cell device comprising a compound having general formula (I) according to the present invention, such as... Figure 7 As shown, the device, from bottom to top, includes: a transparent conductive layer S1 grown on a substrate (not shown in the figure); a hole transport layer S2; a first SAM S31; a perovskite active layer S41; a second SAM S32; an electron transport layer (ETL) S5; and a metal electrode S7.

[0184] In this embodiment, the hole transport layer S2 is made of V2O5, and there is no interface layer S6. The first SAM S31 can passivate surface defects in the hole transport layer, adjust the work function, and promote charge separation and transport at the interface. Similar to the above embodiments, the SAM materials in the first SAM S31 and the second SAM S32 in this embodiment can be the same or different. The first SAM S31 and / or the second SAM S32 include compounds having general formula (I) according to the present invention.

[0185] Example 13

[0186] This embodiment tested the performance of a solar cell device comprising the compound according to the present invention. The sample was tested at AM1.5G, 100mW / cm². 2 The JV performance curve of the battery was tested under illumination, and the following parameters were obtained: open-circuit voltage (Voc), short-circuit current density (Jsc), fill factor (FF), power conversion efficiency (PCE), and stability. The specific test results are shown in Table 1 below.

[0187] Table 1. Performance test results of solar cells

[0188]

[0189] The test results in Table 1 show that the photoelectric conversion efficiency of the perovskite solar cell including the SAM according to the present invention is significantly improved compared with that of the perovskite solar cell without SAM.

[0190] The compounds of general formula (I) according to the present invention use triphenylamine as the core and introduce functional groups such as phosphate groups at various active sites, thereby deriving a series of triphenylamine-type SAM materials with self-assembly capabilities. The compounds according to the present invention possess excellent hole transport, self-spreading, and anchoring capabilities, and can be widely used to modify the transparent conductive layer, light-absorbing layer, and hole transport layer of solar cells to effectively improve charge transport at the interfaces of each layer and passivate vacancy defects on the surface of each layer.

[0191] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a solar cell, characterized in that, Includes the following steps: A transparent conductive layer is grown on the substrate; A first SAM comprising a compound having the general formula (I) is prepared on the transparent conductive layer; Preparation of light-absorbing layer; Preparation of metal electrodes; The general formula (I) is as follows: R1 is selected from alkyl groups having 1 to 10 carbon atoms, olefins having 1 to 10 carbon atoms, or alkyl groups having 1 to 10 carbon atoms including 1 to 3 heteroatoms selected from S, N, or O. R2 is selected from alkyl groups having 1 to 10 carbon atoms; R3 is selected from -COOR4, -CONHR4, -CON(R4)2-SONHR4, -SON(R4)2, -SO2NHR4 or -SO2N(R4)2; R4 is selected from alkyl groups having 1 to 10 carbon atoms.

2. The preparation method according to claim 1, characterized in that, In the compound, R1 is selected from alkyl groups having 1 to 6 carbon atoms or including 1 to 3 alkyl groups having 1 to 6 carbon atoms selected from S, N or O heteroatoms; R2 is selected from alkyl groups having 1 to 5 carbon atoms; and R4 is selected from alkyl groups having 1 to 5 carbon atoms.

3. The preparation method according to claim 1, characterized in that, In the compound, R1 is selected from a straight-chain alkyl group having 1 to 3 carbon atoms or an alkyl group having 1 to 3 carbon atoms including a heteroatom selected from S, N or O.

4. The preparation method according to claim 1, characterized in that, In the compound, R2 is selected from straight-chain alkyl groups having 2 to 4 carbon atoms.

5. The preparation method according to claim 1, characterized in that, In the compound, R4 is selected from straight-chain alkyl groups having 2 to 4 carbon atoms.

6. The preparation method according to any one of claims 1 to 5, characterized in that, It also includes preparing a hole transport layer on the transparent conductive layer before preparing the first SAM, such that the first SAM is disposed between the hole transport layer and the light absorption layer, and preparing the hole transport layer by spin coating, blade coating, slot deposition, spraying, evaporation, magnetron sputtering or electrochemical deposition.

7. The preparation method according to any one of claims 1 to 5, characterized in that, The first SAM was prepared by spin coating, blade coating, slot deposition, spraying, solution dip coating, or vapor deposition.

8. The preparation method according to any one of claims 1 to 5, characterized in that, It also includes preparing an electron transport layer on the light absorption layer, such that the electron transport layer is disposed between the light absorption layer and the metal electrode, and the electron transport layer is prepared by spin coating, blade coating, slot deposition, spraying, vapor deposition, magnetron sputtering or electrochemical deposition.

9. The preparation method according to claim 8, characterized in that, It also includes preparing a second SAM on the light-absorbing layer, such that the second SAM is disposed between the light-absorbing layer and the electron transport layer, the second SAM being made of the compound having the general structural formula (I), PTAA-type SAM material, 2PACz-type SAM material or ImAcHCl.

10. The preparation method according to any one of claims 1 to 5, characterized in that, The light-absorbing layer is made of cuprous oxide, perovskite material, or organic active material.

11. The preparation method according to any one of claims 1 to 5, characterized in that, The light-absorbing layer is made of perovskite material. In this case, the light-absorbing layer is a perovskite active layer. The perovskite film is prepared by a one-step or two-step method and then annealed to obtain the perovskite active layer.

12. The preparation method according to claim 10, characterized in that, The perovskite material has the general molecular structure formula ABX3, wherein A is selected from one or more of methylamine ion, formamidinium ion, phenethylamine ion, 1-naphthylmethylamine ion, and cesium ion; and B is selected from Pb. 2+ and Sn 2+ One or more of them; X is selected from I - ,Br - and Cl - One or more of them.

13. The preparation method according to claim 11, characterized in that, The one-step method includes preparing the perovskite film using a wet or dry method.

14. The preparation method according to claim 13, characterized in that, The wet process includes first preparing a perovskite precursor solution, and then preparing the perovskite thin film from the perovskite precursor solution by spin coating, blade coating, spray coating or inkjet printing; the dry process is vapor deposition, physical vapor deposition or chemical vapor deposition.

15. The preparation method according to claim 11, characterized in that, The two-step method includes first preparing a first perovskite precursor film using the inorganic phase of the perovskite material; and then forming a second perovskite precursor film on the first perovskite precursor film using the organic phase of the perovskite material. The first perovskite precursor film and the second perovskite precursor film constitute the perovskite active layer.

16. The preparation method according to claim 15, characterized in that, The first perovskite precursor film and the second perovskite precursor film are prepared using wet or dry methods. The wet process includes first preparing a perovskite precursor solution, and then preparing the perovskite precursor solution into the first perovskite precursor film or the second perovskite precursor film by spin coating, blade coating, spray coating or inkjet printing; the dry process is vapor deposition, physical vapor deposition or chemical vapor deposition.

17. The preparation method according to claim 15, characterized in that, In the two-step method, the process of preparing the second perovskite precursor film using a wet method includes: mixing the organic phase of the perovskite material with the compound having general formula (I) to prepare a perovskite precursor solution.

18. The preparation method according to claim 17, characterized in that, In the perovskite precursor solution, the concentration of the compound is between 0.1 mg / mL and 1.0 mg / mL.

19. The preparation method according to claim 8, characterized in that, The method also includes preparing an interface layer on the electron transport layer, such that the interface layer is disposed between the electron transport layer and the metal electrode, and preparing the interface layer by spin coating, blade coating, slot deposition, spraying, vapor deposition, magnetron sputtering or electrochemical deposition.

20. The preparation method according to claim 11, characterized in that, The annealing temperature is between 100°C and 150°C, and the annealing time is between 10 min and 30 min.

Citation Information

Patent Citations

  • Halogenated perovskite solar cell and bottom interface self-growth modification method thereof

    CN114665026A

  • Photosensitizer for photovoltaic cell, and photovoltaic cell prepared from same

    KR1020080083522A